(untitled) (Al-Academy, 2016)
Environmental Control Systems form one of the integral tasks of the designer, resulting from his/her acquaintance with the nature of sites and the way they are deployed to achieve modern space entity which is witnessing significant development in the field of interior design.Good deployment of these systems offer us, as designers, high potential and several varied solutions to configure internal spaces characterised as a fertile field of study and knowledge.The research problem was identified in the marginalisation of the importance of Environmental Control Systems as an important designing factor to achieve integrated design. The research problem was demonstrated in Chapter One, along with defining the objectives and formulating the research hypotheses.Chapter Two contained the research theoretical framework, which consists of a review of overall design trends and options when addressing Environmental Control Systems, by studying the most important influential factors of these systems, followed by key indicators derived from the theoretical framework which were, then, utilised in subsequent research procedures. In Chapter Three comes the stage of identifying the research methodology, the research community and the research sample, represented by two samples, and collecting information about them. The research tool was developed through what is construed from the theoretical framework.Chapter Four represented analysis of the content of selected research sample and results of the research were demonstrated, and, in light of these results, the research came out with findings which identified and explained the main differences resulting from deploying the best processors for Heating and Cooling Systems and, therefore, the most important design proposals and recommendations were identified to reach approved design decisions and utilising them to acquire a design product which achieves its objective